Estrategias de Mitigación de Riesgo Ergonómico al Personal del Área de Cocina en el Hotel GHL Villavicencio (2020)
Musculoskeletal disorders, as a consequence of ergonomic risk factors, in workers in the hotel sector in Villavicencio, have been little studied, making the sector a service in poor working, employment and health conditions. This study is descriptive in which data was collected on the tasks carried out in the workplace, in the kitchen area at the hotel, the GHL, using the observation technique. It can be said that the working population in the kitchen area are mostly women and that their ages range between 26 and 45 years. Through the direct interview technique, it can be identified that the workers have symptoms of musculoskeletal pain, as well as It was possible to determine what are the inappropriate postures and the misuse of working conditions in the hotel organization. Likewise, it was observed that with the application of the REBA method, a high score is found in some tasks, which merits immediate action.